EKSPERIMENTASI MODEL ASSESSMENT FOR LEARNING (AfL) MELALUI STRATEGI PEMBERIAN BALIKAN DAN AfL MELALUI TEKNIK BERTANYA YANG EFEKTIF DITINJAU DARI KECERDASAN INTRAPERSONAL PADA SISWA SMP/MTs KELAS VII SE-KOTA SURAKARTA TAHUN PELAJARAN 2013/201 - R, Tika Karlina; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
achievement, students are given Assessment for Learning (AfL) through providing feedback, Assessment for Learning (AfL) through asking effective questions or direct learning model, (2) which has better learning achievement, students with intrapersonal intelligence of high, moderate or low, (3) which has better learning achievement, students are given Assessment for Learning (AfL) through providing feedback, Assessment for Learning (AfL) through asking effective questions or direct learning model in each intrapersonal intelligence, (4) which has better learning achievement, students with intrapersonal intelligence of high, moderate or low on each learning model. The research was a quasi-experimental research with 3x3 factorial designs. The populations were the students of SMP/MTs in Surakarta on academic year 2013/2014 which consisted of 79 SMP/MTs. The size of the sample was 224 students. The instruments used were mathematics achievement test and a questionnaire of student’s intrapersonal intelligence. The data was analyzed using two ways ANOVA. According to the research results, it can be concluded: (1) AfL model through providing feedback had better mathematics achievement than AfL through asking effective questions and direct learning model, whole AfL through asking effective questions had better mathematics achievement than direct learning model, (2) the high intrapersonal intelligence students had better mathematics achievement than the moderate and low intrapersonal intelligence students, while the moderate intrapersonal intelligence students had better mathematics achievement than the low intrapersonal intelligence students, (3) for high and moderate intrapersonal intelligence, the students’ mathematics achievement treated by AfL through providing feedback better than students treated by direct learning model; for low intrapersonal intelligence, all the three models had the same mathematics achievement, (4) for AfL model through providing feedback, the students’ mathematics achievement which have high intrapersonal intelligence better than low intrapersonal intelligence; for AfL model through asking effective questions, the students’ mathematics achievement which have high intrapersonal intelligence better than moderate intrapersonal intelligence, the students’ mathematics achievement which have moderate intrapersonal intelligence better than low intrapersonal intelligence; for direct learning model, students with intrapersonal intelligence of high, moderate and low had the same mathematics achievement.Keywords: Assessment for Learning (AfL), providing feedback, asking effective questions, intrapersonal intelligence, learning achievement.